INDONESIAN DOCUMENTARY: A THEORETICAL REVIEW OF TRUTH CLAIMS PERSPECTIVE - Renta Vulkanita Hasan (Institut Seni Indonesia Yogyakarta, 2020)
Documentary is a type of film that tends to be defined as a recording of reality that embedded in moving images. Documentary cannot be separated from the role of the filmmaker because they constructed reality and issues by assembling footage into narratives. Narratives are that accompanied by the social realm as fact and the role of filmmakers in the documentary brings a notion toward truth claim. Truth claims on the documentary need to be investigated because it involves two aspects: fact and filmmakers. Investigations are conducted to look for possibilities, whether another side of documentary is about trustworthiness. The first step of the investigation is to conduct a theoretical review. Theoretical review is needed in order to find previous research that have notions about truth claim of documentary from another perspective. The method of this investigation is that comparing some previous approaches with cognitive film approach where are from being initially put on the elements of reality and filmmakers, shifted to the perspective placed on the filmic element by engaging the audience. This research has an outcome that is possible to shift perspective from truth claim into trustworthiness through the filmic element that evokes the audience's experience through film clues.